Pengaruh Media Animasi Oleh Guru PAK Terhadap Minat Belajar Siswa Kelas VIII SMP Negeri 2 Sipoholon Kabupaten Tapanuli Utara Tahun Pembelajaran 2023/2024 - Rahmat Simbolon; Tiurma Barasa; Tianggur Medi Napitupulu (Jurnal Pendidikan Agama dan Teologi, 2024)
The aim of this research is to determine the positive and significant influence of the Influence of Animation Media on the Learning Interest of Class VIII Students of SMP Negeri 2 Sipoholon, North Tapanuli Regency for the 2023/2024 Academic Year. The method used is an inferential descriptive quantitative research method, with a population of 123 students and a sample taken of 50% so that the sample for this research is 62 students using Random Sampling techniques.The instrument used in this research used a closed questionnaire of 36 questions, of which 15 questionnaire items were for variable X and 21 items were for variable Y which had been tested on 30 students outside the research sample. The results of the research show that there is a positive and significant influence between the Influence of Animation Media on the Learning Interest of Class VIII Students of SMP Negeri 2 Sipoholon, North Tapanuli Regency for the 2023/2024 Academic Year. 1) Test the relationship between rcount > rtable, namely 0.557 > 0.254, meaning there is a positive relationship between the influence of animation media on students' learning interest; 2) The significant test tcount>ttable is 5.194>2.000, meaning there is a significant relationship between the influence of animation media on students' learning interest; 3) The determination test is 31.02%, meaning that 31.02% of interest in learning is influenced by animation media; 4) The regression equation is obtained from the more Animation Media increases, the more Student Learning Interest increases; 5) Test the hypothesis using a test F is obtained Fcount > Ftable = ( = 0,05,dk numerator k =9,dk denominator = n-2 = 62-2 = 60) that is 26,884 > 2,04. Thus, Ha, namely that there is a positive and significant influence between the Influence of Animation Media on the Learning Interest of Class VIII Students of SMP Negeri 2 Sipoholon, North Tapanuli Regency, for the 2023/2024 Academic Year is accepted and H0 is rejected.